Modeling of cutting speed (CS) for HSLA steel in wire electrical discharge machining (WEDM) using moly wire. (2nd October 2016) - Azam, Muhammad; Jahanzaib, Mirza; Abbasi, Junaid Ali; Wasim, Ahmad
Abstract: The high capital costs of wire electrical discharge machining (WEDM) equipment necessitate optimal utilization of the WEDM process and equipment. Cutting speed (CS) is a key performance measure to achieve this objective. However, process parameters of WEDM greatly hamper CS and hence productivity and machining efficiency. It is therefore essential to pick the right combination of parameters to attain better CSs. In this paper, five process parameters which include pulse on-time, pulse off-time, pulse frequency, power, and wire speed were used to develop an empirical relationship between process parameters and CS. A regression model based on experimental data was developed and validated through confirmation tests. Experiments have been conducted on high-strength low-alloy steel using molybdenum wire. Analysis of variance was applied to segregate significant process parameters and it was revealed that pulse off-time, power, and pulse frequency were the major parameters affecting CS. Contour plots have been established to select the best process parameters in addition to the developed model. Stability of moly wire was also explored using scanning electron microscope and energy dispersive spectroscopy analysis. Results showed that moly wire retains its original surface quality and dimensions which contributes to dimensional accuracy of parts.